The Impact of Artificial Intelligence on Auditing and Accounting Professions: Opportunities for SMEs in Palestine - Abueid, Raed; Arwani, Agus; Devy, Happy Sista (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study investigates AI's impact on these professions within the Palestinian SME sector, emphasizing its role in optimizing operational efficiency and decision-making processes. The rapid advancement of artificial intelligence (AI) has profoundly reshaped professional domains, particularly accounting and auditing. Given the increasing integration of AI into financial operations, a nuanced understanding of its implications for auditing accuracy, regulatory compliance, and overall financial governance is imperative. Anchored in the theoretical frameworks of digital transformation and AI-driven decision support systems, this research assesses AI’s capacity to enhance audit quality and financial reporting precision while examining SMEs’ adaptive strategies in a technologically evolving landscape. Using a quantitative methodology, data were collected from 50 auditors, with 30 valid responses analyzed through logistic regression and Pearson correlation. The findings reveal a strong positive correlation between AI adoption and improvements in auditing and accounting performance, particularly in terms of accuracy, efficiency, and risk management. However, inadequate infrastructure and limited AI expertise remain significant challenges. These findings underscore the critical need for targeted investments in AI literacy, regulatory adaptation, and infrastructural development to fully harness AI’s potential. This study contributes to the growing discourse on AI in financial professions and highlights the need for strategic policies to optimize AI implementation in SMEs.